Wi-Fi Remote Control Car Via Mobile Device - Hoong, Chan Chung (2013)
The goal of this project was to design and build a Wi-Fi Remote Controlled Car via Mobile device. The idea was to first design the interface of the application, settings, camera live view and their overall purposes. Using our own previous knowledge of programming in general combined with X-code programming language. I plan to come out an idea of an automobile controlled, using accelerometers. In order to do this, we need a remote control that using wirelessly transmits that used RF technology, and data to the vehicle to move in any way. Moreover, it is also contain an automatic mode, which the car moves in the direction that control by the user. Mobile device screen is located on the remote control to displays the direction, mode and distance to plan on the distance, direction and mode by a button. By doing this project, I found that there are several problem need to overcome as currently remote control car is not using accelerometer. Finally, all of us all like to play with remote controlled vehicles.